2022
DOI: 10.3390/microorganisms10071364
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characterization of Extended-Spectrum β-Lactamase- and Carbapenemase-Producing Enterobacterales from Tunisian Seafood

Abstract: Aquaculture is a rapidly expanding sector in which it is important to monitor the occurrence of multi-drug resistant (MDR) bacteria. The presence of extended-spectrum β-lactamase (ESBL-) or carbapenemase-producing Enterobacterales is a commonly used indicator of the resistance burden in a given sector. In this study, 641 pieces of farmed fish (sea bream and sea bass), as well as 1075 Mediterranean clams, were analyzed. All ESBL- and carbapenemase-producing Enterobacterales collected were whole-genome sequenced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…A study from Taiwan [44] showed that 28% of the clinical isolates were resistant to an extended-spectrum cephalosporin. Our analysis suggests that bivalve mussels have the potential to act as reservoirs for multidrug-resistant bacteria, which is consistent with the findings of Sola et al [45]. This suggests that increased organic and inorganic contamination in sewage effluents may result in a high load of Aeromonas spp.…”
Section: Discussionsupporting
confidence: 92%
“…A study from Taiwan [44] showed that 28% of the clinical isolates were resistant to an extended-spectrum cephalosporin. Our analysis suggests that bivalve mussels have the potential to act as reservoirs for multidrug-resistant bacteria, which is consistent with the findings of Sola et al [45]. This suggests that increased organic and inorganic contamination in sewage effluents may result in a high load of Aeromonas spp.…”
Section: Discussionsupporting
confidence: 92%
“…Aquatic environments have been identified as reservoirs for antibiotic resistance due to the improper use and excessive administration of antibiotics for disease management [ 47 ]. Recent reports have underscored the emergence of carbapenem-resistant K. pneumoniae (CRKP), even in marine bivalves, posing a disturbing trend in antibiotic resistance [ 29 , 48 ]. Among the confirmed K. pneumoniae isolates tested against the carbapenem antibiotics group, two showed sensitivity, one exhibited intermediate resistance, and thirteen displayed carbapenem resistance.…”
Section: Discussionmentioning
confidence: 99%